E-tourism, as display of dominant criterion of modern tourism-operating: relevant provisions, tools, use - Tatyana Tkachenko; Lesia Kovalska (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
Modern world tourism has become an information-dependent industry. At the moment, there is a rapid trend in the transformation of the society into developed information society. Therefore, the logical goal of the work is to research innovative trends in the development of intelligent web services to create and formulate recommendations for the further development of the tourism industry. The methodological part of the article is based on the use of modern information technologies in the field of tourism, focused on the basis of eРlatforms of the tourism industry. As a result, in many tourist enterprises of the 21st century, significant adaptations must be made to remain solvent and profitable. The effectiveness of the research can be traced to the bright trend of transformation in the world, and in particular in Ukraine, the traditional tourism industry, the e-tourism industry. Scientific novelty consists of conceptual improvement of the manifestation of the dominant criterion of modern tourism operating and its derivatives: e-tourism can be defined as the analysis, development, formation, implementation and application of IT solutions and e-commerce in the world and national tourism industry. Practical significance of the research results is relevant: the need for perfect managers able to manage the tourism business, integrate information and communication technologies (ICT) within the company, to anticipate and promote ICT developments to better meet the needs of the tourism business.